Efficacy and safety of dexamethasone or triamcinolone in combination with anti-vascular endothelial growth factor therapy for diabetic macular edema: A systematic review and meta-analysis with trial sequential analysis - Bo Zhou; Hua Liu; Feng Xiong (PLoS ONE, 2025)
Background The clinical efficacy of anti-vascular endothelial growth factors (anti-VEGFs), corticosteroids, and their combined treatment for diabetic macular edema (DME) has been substantiated by numerous studies. However, it remains uncertain whether the therapeutic benefits of the combined treatment with corticosteroids and anti-VEGFs is superior to those of anti-VEGF monotherapy. Consequently, we conducted a meta-analysis to compare the efficacy and safety of combined treatment with dexamethasone or triamcinolone and anti-VEGF versus anti-VEGF monotherapy in DME treatment. Methods An exhaustive search of the literature was performed on February 23, 2024, scanning through the databases including PubMed, Web of Science, Embase, and the Cochrane Library, with the aim of identifying all relevant studies. The combined results for efficacy and safety were analyzed using the standard mean difference (SMD) and relative risk (RR), both of which were presented with 95% confidence interval (CI). The assessment of heterogeneity was conducted via Cochran’s Q test, I2 statistics, and the implementation of a 95% prediction interval (PI). All analyses were performed by R 4.3.1, Stata 12.0, and TSA v0.9.5.10 Beta software. Results This meta-analysis incorporated 21 eligible studies. The overall analysis revealed that combined treatment of dexamethasone or triamcinolone with anti-VEGF agents did not demonstrate superiority over anti-VEGF monotherapy in improving best-corrected visual acuity (BCVA) (Dexamethasone: SMD -0.266, 95% CI -1.001 to 0.468, 95% PI -2.878 to 2.346; Triamcinolone: SMD -0.340, 95% CI -1.230 to 0.550, 95% PI -3.554 to 2.874) and reducing central macular thickness (CMT) (Dexamethasone: SMD -1.255, 95% CI -2.861 to 0.350; Triamcinolone: SMD -0.207, 95% CI -0.895 to 0.481, 95% PI -2.629 to 2.215). However, the combination therapy significantly increased the risk of elevated intraocular pressure (RR 5.783, 95% CI 3.007 to 11.121, 95% PI 0.520 to 56.931) and ocular hypertension (RR 8.885, 95% CI 2.756 to 28.649, 95% PI 1.262 to 39.208). Subgroup analysis suggests that dexamethasone plus anti-VEGF therapy showed a greater reduction in central subfield thickness (SMD -0.440, 95% CI -0.755 to -0.126) compared to anti-VEGF monotherapy among patients with persistent DME. Conclusion Our study confirmed that dexamethasone or triamcinolone plus anti-VEGF therapy did not show superior efficacy in improving BCVA and reducing CMT in DME patients compared with anti-VEGF monotherapy. Clinicians should weigh the pros and cons comprehensively when implementing combined therapy.